ANALYSIS ON SUSTAINABILITY OF TOURISM BUSINESS - Faradesi Ardialisa; Aji Hermawan; M. A Chozin (School of Business, Bogor Agricultural University (SB-IPB), 2012)
The objectives of the research were to understand indicators of business sustainability tourism from stakeholders’ perspectives in relation to 3P (People, Planet, Profit), to understand how the concept of sustainability is operationalized in the Pancawati group in relation to 3P (People, Planet, Profit), and to map the value chain of Lembur Pancawati as the case in Ecotourism in Bogor. The methodology used was qualitative descriptive practice-oriented business research with single case study. Based on the stakeholder analysis in Bogor tourism, the indicators of sustainable business in tourism are: (i) Involvement from local people, (ii) Preservation of nature and local culture, (iii) Availability of nature Education program, (iv) Strong commitment from business owner/leader, (v) Sufficient capital to support the initial business establishment, (vi) Availability of various networks. The operationalization in Pancawati Group was observed to have item i, iii, and iv partially implemented and the rest was fully implemented. The position of Pancawati Group in value chain was as main firm, as it acted as multiple actors in the chain. In order to have all indicators implemented, it was suggested to have public private partnership in place.Keywords: Sustainable Tourism, Value Chain, Qualitative Methods